Disorders of the limbs. III. Hands and feet. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
Virus-induced diseases (continuation) Some virus exanthemata with prominent acrolocated involvement, are reminiscent of staphylococcal and streptococcal scarlet fever due to the large sheets of scale (Fig. 1824, 1826), which are present in both disorders, whereas other virus exanthemata, sometimes due to Parvovirus B19 (8), with erythema, edema and scaling prevailing on acrolocated areas, thus on hands (Fig. 1825, 1827) and feet, are reminiscent of Kawasaki disease.